Modelling the crack growth behaviour of a single crystal nickel base superalloy under TMF loading with long dwell times. (March 2021) - Palmert, Frans; Almroth, Per; Gustafsson, David; Loureiro-Homs, Jordi; Saxena, Ashok; Moverare, Johan
Highlights: The influence of hold time on IP-TMF crack growth is evaluated for an SX superalloy. The creep crack growth rate da/dt displays a strong correlation with Ct . The relationship between da/dt and Ct is temperature independent. A superposition model based on Ct and ΔKeff successfully describes the overall da/dN . The model was fitted to isothermal tests and yields accurate predictions for IP-TMF. Abstract: The influence of hold time on the crack growth behaviour of a single crystal nickel base superalloy under in-phase thermomechanical fatigue is investigated. Two da/dt models were calibrated using creep crack growth tests in the temperature range 750–950 °C: one based on K and the other on ( Ct )avg . The models were applied, in combination with a cycle dependent model, to predict da/dN of in-phase thermomechanical fatigue crack growth tests with 1–6 h hold time. The predictions based on K were inaccurate and generally non-conservative, whereas the predictions based on ( Ct )avg were accurate. da/dt vs ( Ct )avg followed a single trendline for all temperatures.